2022
DOI: 10.1007/s11606-022-07618-x
|View full text |Cite
|
Sign up to set email alerts
|

A Taxonomy of Hospital-Based Addiction Care Models: a Scoping Review and Key Informant Interviews

Abstract: BACKGROUND: There is pressing need to improve hospital-based addiction care. Various models for integrating substance use disorder care into hospital settings exist, but there is no framework for describing, selecting, or comparing models. We sought to fill that gap by constructing a taxonomy of hospital-based addiction care models based on scoping literature review and key informant interviews. METHODS: Methods included a scoping review of the literature on US hospital-based addiction care models and interven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
73
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 62 publications
(73 citation statements)
references
References 111 publications
0
73
0
Order By: Relevance
“…Finally, guidelines do not specify how hospitals should deliver these recommendations. Various approaches to delivering hospital‐based OUD treatment exist, and future work should explore what models best support effective delivery of evidence‐based guidelines 75 …”
Section: Discussionmentioning
confidence: 99%
“…Finally, guidelines do not specify how hospitals should deliver these recommendations. Various approaches to delivering hospital‐based OUD treatment exist, and future work should explore what models best support effective delivery of evidence‐based guidelines 75 …”
Section: Discussionmentioning
confidence: 99%
“…While our study found higher inpatient availability of buprenorphine in South Florida (88%), we identified further hospital policy-level barriers to induction, most often based on provider specialty restrictions. Englander and colleagues described the variety of approaches to hospital-based OUD care, which could include generalists or specialists as the team tasked with OUD treatment [32]. They suggest that formal protocols for opioid withdrawal or treatment are necessary, at a minimum, to help prompt appropriate care.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the local burden of SIRIs and lack of inpatient addiction medicine consult services, we developed an integrated infectious disease/SUD treatment intervention in 2020 called the Jackson SIRI team. Using Englander and colleagues’ taxonomy of hospital-based addiction care, the SIRI team is a hospital-based opioid treatment (HBOT) program , but additionally includes substantial post-hospital care [ 25 ]. The SIRI team intervention provides integrated infectious disease and SUD treatment across the healthcare continuum, starting from the inpatient setting and continuing for 90-days post-hospital discharge.…”
Section: Introductionmentioning
confidence: 99%
“…A multidisciplinary approach that incorporates infectious disease (ID) and addiction care in the hospital and after discharge has the potential to mitigate many of the barriers to successful individual and health system outcomes for patients experiencing SIRIs [20]. Some existing models of integrated ID/SUD teams include ID specialists, addiction medicine specialists, psychiatrists, and surgeons and may incorporate pharmacotherapy, behavioral treatments, harm reduction and post discharge follow-up for patients [21][22][23][24][25]. Previous research has demonstrated that integration of evidence-based addiction treatment-such as medications for opioid use disorder (MOUD)-is associated with fewer patient-directed discharges [26,27], lower readmission rates [21,28], higher rates of antimicrobial therapy completion [26,29], higher post-discharge SUD treatment engagement [30], and reduced substance use at 30 days [31].…”
Section: Introductionmentioning
confidence: 99%